Impact of modified CDC/NHSN surveillance definition on the incidence of CAUTI: a study from an Indian tertiary care hospital. Issue 4 (July 2021) - Behera, Bijayini; Jena, Jayanti; Mahapatra, Ashoka; Biswala, Jyoti
Introduction: Catheter-associated urinary tract infections (CAUTIs) are one of the most common infections encountered in healthcare settings. Candida spp. were excluded as the causative agents of CAUTIs as per Centres for Disease Control and Prevention (CDC) and National Healthcare Safety Network (NHSN) definitions in 2015. Aim: To determine the impact of the 2015 definition change on the CAUTI rate of patients admitted to medical and surgical intensive care units (ICUs) of a tertiary care and teaching hospital in India. Method: CAUTI rates were compared in both the ICUs over a period of two years with inclusion and exclusion of Candida spp. Results: Out of the total 116 CAUTI episodes during the study period, a mean of 9.08 CAUTIs per 1000 catheter days were observed in both the ICUs when Candida spp. were included, but the mean CAUTI rate was reduced to 4.78/1000 catheter days when Candida spp. were excluded. Discussion/Conclusion: The mean CAUTI rate decreased by 46.03% solely by excluding Candida spp. This significant reduction in CAUTI rates may be applicable to institutions having high rates of candiduria in catheterised patients, but may not be applicable in centres where the incidence of candiduria is already low. Disregarding Candida as a causative agent of CAUTI did not impact rates of central line-associated bloodstream infections during the study period.